Glioblastoma cell adhesion properties through bacterial cellulose nanocrystals in polycaprolactone/gelatin electrospun nanofibers. (1st April 2020) - Unal, Semra; Arslan, Sema; Karademir Yilmaz, Betul; Kazan, Dilek; Oktar, Faik Nuzhet; Gunduz, Oguzhan
Highlights: PCL/Gel/BCNC scaffolds were produced by electrospinning with various BCNC ratio. BCNC in PCL/Gel fibers promoted axon growth and elongation glioblastoma cells. PCL/Gel/BCNC1.0 provide a 3D ECM for GBM cells that mimic of the in vivo tumor. Abstract: Glioblastoma (GBM), the most common and extremely lethal type of brain tumor, is resistant to treatment and shows high recurrence rates. In the last decades, it is indicated that standard two-dimensional (2D) cell culture is inadequate to improve new therapeutic strategies and drug development. Hence, well-mimicked three-dimensional (3D) tumor platforms are needed to bridge the gap between in vitro and in vivo cancer models. In this study, bacterial cellulose nano-crystal (BCNC) containing polycaprolactone (PCL) /gelatin (Gel) nanofibrous composite scaffolds were successfully fabricated by electrospinning for mimicking the extracellular matrix of GBM tumor. The fiber diameters in the nanofibrous matrix were increased with an increased concentration of BCNC. Moreover, fiber morphology changed from the smooth formation to the beaded formation by increasing the concentration of the BCNC suspension. In-vitro biocompatibilities of nanofibrous scaffolds were tested with U251 MG glioblastoma cells and improved cell adhesion and proliferation was compared with PCL/Gel. PCL/Gel/BCNC were found suitable for enhancing axon growth and elongation supporting communication between tumor cells and the microenvironment, triggering the process of tumor recurrence. Based on these results, PCL/Gel/BCNC composite scaffolds are a good candidate for biomimetic GBM tumor platform.